Mitochondrial Dysfunction in Huntington’s Disease; Interplay Between HSF1, p53 and PGC-1α Transcription Factors - Intihar, Taylor A.; Martinez, Elisa A.; Gomez-Pastor, Rocio (Frontiers in Cellular Neuroscience, 2019)
Huntington’s disease (HD) is a neurodegenerative disease caused by an expanded CAG repeat in the Htt gene, causing the protein to misfold and aggregate. HD progression is characterized by motor impairment and cognitive decline associated to the preferential loss of striatal medium spiny neurons (MSN). The mechanisms that determine increased susceptibility of MSNs to mutant Htt (mHtt) are not fully understood, although there is abundant evidence demonstrating the importance of mHtt-mediated mitochondrial dysfunction in MSNs death. Two main transcription factors, p53 and the peroxisome proliferator co-activator PGC-1, have been widely studied in HD for their roles in regulating mitochondrial function and apoptosis. The action of these two proteins seems to be interconnected. However, it is still open to discussion whether p53 and PGC-1 -dependent responses directly influence each other or if they are connected via a third mechanism. Recently, the stress responsive transcription factor HSF1, known for its role in protein homeostasis, has been implicated in mitochondrial function and in the regulation of PGC-1 and p53 levels in different contexts. Based on previous reports and our own research, we discuss in this review the potential role of HSF1 in mediating mitochondrial dysfunction in HD and propose a unifying mechanism that integrates the responses mediated by p53 and PGC-1 in HD via HSF1.